Smartphone addiction level among a group of university students - Dikeç, Gül; Kebapçı, Ayda (Journal of Dependence, 2018)
Objective: The objective of this study was to identify the level of smartphone addiction among students from various departments at a foundation university. Method: The sample group consists of 148 female and 117 male students enrolled at a foundation university adding up to a total of 265 students. The data were collected via Qualtrics online survey website by means of Information Form and Smartphone Addiction Scale established after relevant literature review by the researchers. Results: The average age of the participating students was 21.04±2.63, including 55.8% female and 44.2% male students. There were 233 undergraduates, 20 graduates and 12 doctoral students. The average Smartphone Addiction Scale score among students was found to be 84.883 ± 22.96. Accordingly, 136 (51.3%) of the participants were found to be at low risk level, whereas 129 (48.7%) were in the high-risk level.. A significant difference was detected between the average Smartphone Addiction Scale scores among samples pursuant to education levels. Negative relation was put forth between the average Smartphone Addiction Scale scores and the academic GPA, whereas positive significant relation was found between the average scale score and the daily smartphone usage time. Conclusion: The risk of smartphone addiction was found to be greater in comparison with previous studies carried out in Turkey..